Дымообразующая способность кабельных изделий - Dmitrichenko, Александр; Ivanovich, Александр; Chaychits, Николай; Zinkevich, Геннадий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
Article is devoted to a problem of maintenance of fire safety of cable products. Ability to form a smoke is a component of fire danger of the cables, therefore the enhanced attention should be given to the given question. Authors analyze the phenomena resulting to the raised formation of a smoke. It is offered as one of kinds of tests of cables on ability to form a smoke, to carry out in a mode of decay of a cable product, and it is planned to develop a test method, and also to develop criteria of an estimation of results.